Kinetika Hidrolisis Pati Biji Nangka (Artocarpus heterophyllus) Menggunakan Katalisator Asam Klorida (HCl) - Sri Endang; Muh. Yudi; Asri Saleh (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2014)
The research of kinetic hydrolysis from the starch of jackfruit seed (Artocarpus heterophyllus) used clorid acid catalyst (HCl) aims to know the influence of variation of concentration HCl catalyst which give the maximum result of hydrolysis of the starch of jackfruit seed, determining the optimum concentration of HCl catalyst that produces the maximum value of the reaction rate constants, and determine the value of the reaction rate constant of hydrolysis the starch of jackfruit seed using catalyst. The method of this research has done in two stages that are the determination of the optimum catalyst concentration of HCl hydrolysis reaction of the starch of jackfruit seed using various concentration of catalyst HCl 0,5 M; 1,0 M; 1,5 M; 2,0 M and 2,5 M at the optimum temperature and stirring time (90oC during 70 minutes). Hydrolysis followed by neutralization process using sodium hydroxide solution and evaporated to get the form of glucose concentrated, that glucose is analyzed by qualitative and quantitative with Benedict experiment and fenol sulphate acid method, based on maximum degree of glucose which is gotten from the result of hydrolysis the starch of jackfruit seed variation concentration oh HCl is in HCl 1,5 M concentration with degree of glucose (% weight) is 7,54% with percentage of starch conversion is 83,21%. Second step is determining the value of hydrolysis constant rate reaction which use time variation (30, 40,50, 60 and 70) minutes in 70 minutes optimum operation condition, 90oC te mperature and concentration catalyst of HCl 1,5 M. Based on statistic calculation date of ANOVA is gained F hitung < F tabel so Ho receive and reject HI which shows that there is not influence catalyst variation concentration of HCl to the result of hydrolysis the starch of jackfruit seed which is gained. The result of the research shows that hydrolysis of kinetic of the starch of jackfruit seeduse HCl catalyst is reaction of the first apparent orde with value of the reaction constant rate k = 0,0216 minutes-1.